Vigilance towards raptors by nuclear species in bird mixed flocks in a Brazilian savannah - Ragusa-Netto, J. (Swets Zeitlinger Publishers, 2002)
A nuclear or leader species is the one around which foraging activity is organized. In the campo-cerrado (Brazilian savannah) up to four bird species (Saltator atricollis, Cypsnagra hirundinacea, Mimus saturninus, and Neothraupis fasciata) may function as nuclear or leader species in mixed species flocks. The aim of this study was to assess the features shown by these nuclear species. I quantified parameters of sociality, communication and alertness of nuclear bird species in mixed flocks with different composition. Parameters related to sociality (mean intraspecific group size) and communication (frequency of contact calls) were not correlated with the leadership. on the other hand, the most alert species was in the front of a given mixed flock most of the time. The leader species spent more time in vigilance and gave most alarm calls due to approaching raptors earlier. The results of this study strongly suggest that the alertness of a species is the major character of nuclear bird species in mixed flocks of the campo-cerrado.
Keywords: mixed flocks; sentinels; vigilance; nuclear species; Brazilian savannah